PENGARUH KEPEMILIKAN MANAJERIAL, UKURAN PERUSAHAAN DAN REPUTASI AUDITOR TERHADAP OPINI AUDIT GOING CONCERN - Sihite, Debby Alfani; Hasanah, Neneng (Publika Citra Media, 2024)
This research aims to examine the influence of managerial ownership, company size, and auditor reputation on Going Concern Audit Opinions in Companies that are Members of the Jakarta Islamic Index 70 for the 2018-2022 Period. This research uses a quantitative approach and uses associative methods. The type of data used in this research is secondary data. The data analysis method used in this research is Logistic Regression Analysis using the e-views version 10 application and Microsoft Excel. The data collection technique in this research is a purposive sampling technique with 70 populations being the 19 company samples processed in this research. The research results show that simultaneously managerial ownership, company size and auditor reputation influence going concern audit opinion. Partially, managerial ownership and company size have no effect on going concern audit opinion, while auditor reputation has no effect on going concern audit opinion.